2019
DOI: 10.1037/pspp0000174
|View full text |Cite
|
Sign up to set email alerts
|

The development of narcissistic admiration and machiavellianism in early adulthood.

Abstract: We investigated the development of narcissistic admiration (i.e., the assertive or extraverted dimension of narcissism; Back et al., 2013) and Machiavellianism (Mach) in early adulthood. Specifically, we examined (a) mean-level changes in narcissistic admiration and Mach during early adulthood and (b) how studying economics and experiencing any of 30 life events were related to individual differences in changes in narcissistic admiration and Mach. We used longitudinal data from 2 cohorts of young adults in Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 83 publications
(119 reference statements)
7
45
1
Order By: Relevance
“…The latter result was attributed to narcissistic individuals' toxic interpersonal style (Raskin & Terry, 1988) and impulsivity (Vazire & Funder, 2006). Similarly, Grosz et al (2017) found that young adults higher in narcissistic admiration experienced more negative agentic events (i.e., events that participants evaluated negatively and that experts rated as high in agency, such as those "related to competence, extraversion, uniqueness, separation, and focus on the self," p. 3).…”
Section: Does Narcissism Predict Life Events and Circumstances? -Selementioning
confidence: 94%
“…The latter result was attributed to narcissistic individuals' toxic interpersonal style (Raskin & Terry, 1988) and impulsivity (Vazire & Funder, 2006). Similarly, Grosz et al (2017) found that young adults higher in narcissistic admiration experienced more negative agentic events (i.e., events that participants evaluated negatively and that experts rated as high in agency, such as those "related to competence, extraversion, uniqueness, separation, and focus on the self," p. 3).…”
Section: Does Narcissism Predict Life Events and Circumstances? -Selementioning
confidence: 94%
“…Unfortunately, it has been difficult to draw many conclusions from the studies that have examined longitudinal changes in narcissism across life. For example, studies of individuals followed over 4-and 10 years during young adulthood reveal declines in narcissism, providing some support for the social investment model's prediction of increased maturity as young adulthood ends (K. S. Carlson & Gjerde, 2009;Grosz et al, 2017). Studies beyond adulthood are exceptionally rare.…”
Section: Limitations Of the Current Literaturementioning
confidence: 99%
“…Hence, we responded to recent calls in management (e.g., Grijalva & Harms, 2014;Tasselli et al, 2018) and personality (e.g., Grosz et al, 2019) literatures to investigate the developmental paths of this critical domain of personality functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, such age differences have mainly been used to inform the debate on the (non-)existence of generational differences in narcissism (e.g., Roberts et al, 2010;Trzesniewski, Donnellan, & Robins, 2008a;2008b). In addition to this cross-sectional work, and more relevant to the current study, a handful of investigations have looked at within-person changes in narcissism using longitudinal designs in which participants are tracked across several years during young adulthood (i.e., under age 30) (Carlson & Gjerde, 2009;Grosz et al, 2019;Orth & Luciano, 2015). Across all three studies, virtually no mean-level intraindividual change in narcissism was observed during early adulthood.…”
Section: Reciprocal Relationships Over Two Decadesmentioning
confidence: 99%
See 1 more Smart Citation